Towards a dialogical anthropology - Grubačić, Andrej (Anthropological notebooks, 2021)
This article argues that a holistic reading of David Graeber’s oeuvre reveals a coherent and systematic intellectual and political project. We argue that his theories, public interventions, analyses, or ideas scattered across different (sub)disciplines, formats, and topics as diverse as non-state spaces, anarchist anthropology, democracy, mutual aid, debt, bureaucracy, bullshit jobs, kings and a different understanding of history and the development of science, should be understood as a well-considered and systematic attempt to reimagine and reposition the role of scholarship in a search for a radically different political and economic model. We focus on dialogue as the centre of both Graeber’s scholarship and politics. For Graeber, dialogue has always been the primary anthropological method, not only in terms of fieldwork but also in the context of the collective or dialogic emergence of ideas. At the same time, dialogue is the very core of his politics as a collective attempt to reconcile unconsummatable perspectives in a practical situation of action. Finally, we explore Graeber’s idea of care and freedom as a new political and economic paradigm. We consider Graeber’s simple and yet infinitely complex question: why not use the ideas of care and freedom, instead of production and consumption, as a basis for political economy, which should, after all, only be a way to take care of each other?
Keywords: Anarhizem; Antropologija; Dialog; Graeber, David; Svoboda